2004
DOI: 10.1016/j.virol.2003.09.033
|View full text |Cite
|
Sign up to set email alerts
|

DNA immunization with a herpes simplex virus 2 bacterial artificial chromosome

Abstract: Construction of a herpes simplex virus 2 (HSV-2) bacterial artificial chromosome (BAC) is described. BAC vector sequences were inserted into the thymidine kinase gene of HSV-2 by homologous recombination. DNA from cells infected with the resulting recombinant virus was transformed into E. coli, and colonies containing the HSV-2 BAC (HSV2-BAC) were isolated and analyzed for the expected genotype. HSV2-BAC DNA was infectious when transfected back into mammalian cells and the resulting virus was thymidine kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…JQ780693]). While three HSV-1 BAC clones (which have no viral genes deleted or mutated in the viral backbone) are available for HSV-1 mutagenesis studies (17,27,48), the HSV-2 BAC clones that have been reported are not optimal for pathogenesis studies in animals because the virus backbones in these BAC clones have one or more genes deleted (34,41). Therefore, we developed a BAC clone that could be used to generate virus with minimal extraneous sequences and that would be inserted into a site in the genome that should not affect virus replication or pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JQ780693]). While three HSV-1 BAC clones (which have no viral genes deleted or mutated in the viral backbone) are available for HSV-1 mutagenesis studies (17,27,48), the HSV-2 BAC clones that have been reported are not optimal for pathogenesis studies in animals because the virus backbones in these BAC clones have one or more genes deleted (34,41). Therefore, we developed a BAC clone that could be used to generate virus with minimal extraneous sequences and that would be inserted into a site in the genome that should not affect virus replication or pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used in several human herpesviruses, including HSV-1 (17,27,48), HSV-2 (34, 41), varicella-zoster virus (VZV) (39,53,63,64), Epstein-Barr virus (EBV) (10,42), cytomegalovirus (CMV) (3,7), human herpesvirus 6 (HHV-6) (2,49), and Kaposi's sarcoma-associated herpesvirus (KSHV) (65), and greatly simplifies herpesvirus mutagenesis. The HSV-2 BAC clones that have been reported are not optimal for pathogenesis studies in animals because the virus backbones in these BAC clones have one or more genes deleted (34,41).…”
mentioning
confidence: 99%
“…Herpesviruses have a large genome size, with numerous nonessential genes which make herpesviruses attractive for gene therapy, as nonessential genes can be substituted with therapeutic genes. Since the analysis of nonessential genes for replication is still dependent on the construction of complementing cell lines, an increase in knowledge of the gene functions of herpesviruses can be expected in the offing, thus promising new possibilities in the use of herpesviruses in gene therapy and vaccine development (Meseda et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The complete removal of the mini-F vector by homologous recombination has been limited to laborious cotransfection experiments or to BAC constructs with restricted stability in bacteria (Strive et al, 2007;Wagner et al, 1999;Yu et al, 2002). Alternatively, the vector elements can be flanked by recognition sites for site-specific recombinases, which leave behind only one small recognition sequence (Adler et al, 2000(Adler et al, , 2001Chang & Barry, 2003;Smith & Enquist, 2000;Strive et al, 2006;Tanaka et al, 2003;Zhao et al, 2008 Horsburgh et al, 1999a, b;Nagel et al, 2008;Saeki et al, 1998;Stravropoulos & Strathdee, 1998;Tanaka et al, 2003Meseda et al, 2004Nagaike et al, 2004Tischer et al, 2007;Wussow et al, 2009;Yoshii et al, 2007;Zhang et al, 2007Brazeau et al, 2011Gray et al, 2011Smith & Enquist, 1999Mahony et al, 2002Robinson et al, 2008 …”
Section: Generation Of Recombinant Large Dna Virusesmentioning
confidence: 99%
“…Many BAC-based studies were performed on mutations in HSV-1 genes (e.g., Boutell et al, 2002;Leege et al, 2009;O'Hara et al, 2010;Roberts et al, 2009;Tong & Stow, 2010). Also, HSV-2 is available as a viral BAC (Meseda et al, 2004). Several strains of the highly cell-associated varicellovirus prototype, VZV, were cloned as infectious BACs, the vaccine and parental OKA strains, as well as the wild-type isolate HJO (Nagaike et al, 2004;Tischer et al, 2007;Wussow et al, 2009;Yoshii et al, 2008;Zhang et al, 2007Zhang et al, , 2008.…”
Section: Functional Mutagenesis Of Specific Viral Bacsmentioning
confidence: 99%